The role of dispersion type metal⋯π interaction in the enantiotropic phase transition of two polymorphs of tris-(thienyl)bismuthine. Issue 39 (27th September 2017) - Preda, A. M.; Schneider, W. B.; Schaarschmidt, D.; Lang, H.; Mertens, L.; Auer, A. A.; Mehring, M.
Abstract : Bi(2-C4 H3 S)3 shows an enantiotropic phase transition that is dominated by London dispersion forces. DFT calculations on model compounds were carried out in order to investigate the competition between Bi⋯S and Bi⋯π heteroarene interaction. Abstract : Two polymorphs of tris(thienyl)bismuthine Bi(2-C4 H3 S)3 (1 ) were isolated upon crystallization from n -hexane at different temperatures. The high temperature form1 -HT crystallized at 269 K in the trigonal space group R 3̄, whereas the low temperature form1 -LT crystallized at 245 K in the triclinic space group P 1̄. An enantiotropic phase transition was observed at 250 K showing a transition energy of 1.4 kJ mol −1 . Both polymorphs reveal the formation of centrosymmetric dimers that are based on London dispersion type bismuth⋯π heteroarene interactions. These primary building units show additional dispersion type interactions between neighbouring dimers and as a result 2D networks are formed. DFT calculations on the model systems BiX3 ⋯π thiophene (X = Cl, Me) verify the hypothesis of a soft and shallow binding potential of the London dispersion type bismuth⋯π heteroarene interaction, providing an explanation for the reversibility of the phase transition.